Noncontact Measurement for Radius of Curvature of Unpolished Lens. (29th September 2014) - Liang, Haifeng
Abstract : A noncontact mathematical model to measure radius of curvature (ROC) of an unpolished spherical lens was proposed and also proved by experiments. This model gives ROC as a function of arcs radii and their separation distance, where the radii of the corresponding arcs could be acquired by taking coordinates of points on the arcs when two parallel lines of light project onto a lens surface. Our experiments demonstrated that the measured maximum relative error was 0.027% for a concave surface with a 38.19 mm ROC and 0.021% for a convex surface with a 97.75 mm ROC, which were all in agreement with those of theory prediction error. The suggested method presented a fast noncontact method for testing ROC of lens during coarse grinding and fine grinding.